Neuroprotection for Amyotrophic Lateral Sclerosis: Role of Stem Cells, Growth Factors, and Gene Therapy - S. Pandya, Rachna; L. J. Mao, Lilly; W. Zhou, Edward; Bowser, Robert; Zhu, Zhenglun; Zhu, Yongjin; Wang, Xin (Central Nervous System Agents in Medicinal Chemistry, 2012)
Various molecular mechanisms including apoptosis, inflammation, oxidative stress, mitochondrial dysfunction and excitotoxicity have been implicated in the pathogenesis of amyotrophic lateral sclerosis (ALS), though the exact mechanisms have yet to be specified. Furthermore, the underlying restorative molecular mechanisms resulting in neuronal and/or non-neuronal regeneration have to be yet elucidated. Therapeutic agents targeting one or more of these mechanisms to combat either initiation or progression of the disease are under research. Novel treatments including stem cell therapy, growth factors, and gene therapy might prolong survival and delay progression of symptoms. Harnessing the regenerative potential of the central nervous system would be a novel approach for the treatment of motor neuron death resulting from ALS. Endogenous neural replacement, if augmented with administration of exogenous growth factors or with pharmaceuticals that increase the rate of neural progenitor formation, neural migration, and neural maturation could slow the rate of cell loss enough to result in clinical improvement. In this review, we discuss the impact of therapeutic treatment involving stem cell therapy, growth factors, gene therapy, and combination therapy on disease onset and progression of ALS. In addition, we summarize human clinical trials of stem cell therapy, growth factor therapy, and gene therapy in individuals with ALS.
Keywords: physical exercise